Vivre de paysage dans le Morvan ou l’impensé de la gestion forestière morvandelle - Damien Marage (Projets de Paysage)
The landscape has become the red thread of the 2020-2035 Charter for the Morvan Regional Nature Park. Stakeholders realise that in considering the future of a forest landscape they need to systemically take into account the activities deployed within it and, above all, to recognise the landscape as an excellent lever for motivation and mediation between actors. By addressing cultural or societal expectations, enhancing the project, and gaining the population’s approval can ensure the landscape is experienced as a living space. A landscape must function in relation to its ecological, socio-economic, and cultural components. If these components evolve in a logical and comprehensible way in tune with a certain "state of the world”, their change is easily accepted. The landscape can therefore no longer be perceived as "the part of a region nature presents to an observer". From this object-subject perspective, the forest landscapes of the Morvan sometimes offer us a spectacle of desolation and emptiness. This coupling of subject and object which is specific to the Western definition of the landscape could be replaced by a vision derived from Chinese thought. We will see how the production of emerging categories based on regional consultation procedures can enable actors to work together on preserving the shared experience of the landscape. The solution to such oppositions lies in the construction of a shared vision of the future of the landscape of the Morvan Massif. We will back up the arguments put forward in this article with the many evaluations and surveys carried out during the revision of the charter.